PENGARUH PROFESIONALISME DAN INDEPENDENSI TERHADAP KUALITAS AUDIT STUDI PADA AUDITOR KANTOR AKUNTAN PUBLIK DI JAKARTATIMUR - Budi Tri Rahardjo, Ak., M.Ak., CA (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2017)
The purpose of this research is to know how to influence the professionalism and independence of the Audit Quality in Public Accounting Firm in East Jakarta wilayah. Data used in this study are primary data. Data analysis technique used is the Multiple Regression Analysis, Analysis of Coefficient of Determination, Correlation Coefficient Analysis and Hypothesis Testing. From these results it can be concluded that after going through the calculation of SPSS, the results obtained correlation calculation in which the magnitude of the correlation coefficient professionalism and independence of the auditor amounted to 0.503, which means the level of satisfaction and confidence have a strong relationship to the purchase decision, with a significance probability of 0.000. It can be concluded that the professionalism and independence has a positive effect on audit quality.